Digging in the City of Brotherly Love : stories from Philadelphia archaeology - Yamin, Rebecca, 1942- (Yale University Press, 2008)
Beneath the modern city of Philadelphia lie countless clues to its history and the lives of residents long forgotten. This intriguing book explores eighteenth- and nineteenth-century Philadelphia through the findings of archaeological excavations, sharing with readers the excitement of digging into the past and reconstructing the lives of earlier inhabitants of the city. Urban archaeologist Rebecca Yamin describes the major excavations that have been undertaken since 1992 as part of the redevelopment of Independence Mall and surrounding areas, explaining how archaeologists gather and use raw data to learn more about the ordinary people whose lives were never recorded in history books. Focusing primarily on these unknown citizens-an accountant in the first Treasury Department, a coachmaker whose clients were politicians doing business at the State House, an African American founder of St. Thomas's African Episcopal Church, and others-Yamin presents a colorful portrait of old Philadelphia. She also discusses political aspects of archaeology today-who supports particular projects and why, and what has been lost to bulldozers and heedlessness. Digging in the City of Brotherly Love tells the exhilarating story of doing archaeology in the real world and using its findings to understand the past.